The contribution of board of directors’ competency, commitment, integrity, and accountability to the timely submission of the annual financial report of agricultural co- operative societies in the state of Perak and the moderating effect of office support and document handling / Hatta Safwan - Safwan, Hatta (Institute of Graduate Studies, UiTM, 2014)
The post-mortem on the National Co-operative Policy 2002-2010 had highlighted, among others, the following weaknesses: low entrepreneurship skills, lack of understanding among members of cooperatives, and lack of professional management. In 1999, 58.8% (97 out of 165) agricultural co-operatives in Perak failed to submit their audited financial report on time as required by the Co-operative Society Act 1993 (Act 503) and Regulations. The targeted key performance indicators (KPI) for the Core Strategic V of National Cooperative Policy 2011 – 2020 requires that at least 90% of the co-operatives have audited annual financial report and 90% of the cooperatives conduct the Annual General Meeting (AGM). This study, which involves the Agricultural Co-operative Societies in Perak, aims to examine the relationship between educational level and training attained with the competency of BODs in ensuring timely submission of financial reporting. A series of tests were carried out to determine the relationship of BODs’ competency, commitment, integrity and accountability with timely submission of financial reporting.